CИСТЕМНИЙ ПІДХІД ДО ФОРМУВАННЯ ВАЛЕОЛОГІЧНОЇ КОМПЕТЕНТНОСТІ ВЧИТЕЛЯ ТА УЧНІВ В УМОВАХ ШКОЛИ КУЛЬТУРИ ЗДОРОВ’Я (Педагогіка вищої та середньої школи, 2022)
The article is devoted to the actual guestions valeological competence of the modern teacher, is explored the structure valeological competence teacer, which is developed on the basis of priority spiritual-valued gualitties teacher, that is deaten back on forming vital jurisdictions undent.